2018
DOI: 10.1038/s41377-018-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Gold-patched graphene nano-stripes for high-responsivity and ultrafast photodetection from the visible to infrared regime

Abstract: Graphene is a very attractive material for broadband photodetection in hyperspectral imaging and sensing systems. However, its potential use has been hindered by tradeoffs between the responsivity, bandwidth, and operation speed of existing graphene photodetectors. Here, we present engineered photoconductive nanostructures based on gold-patched graphene nano-stripes, which enable simultaneous broadband and ultrafast photodetection with high responsivity. These nanostructures merge the advantages of broadband o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 43 publications
0
145
0
1
Order By: Relevance
“…As a result, nonzero net photocurrent can be generated without applying bias voltage, solving the dark current problem. In 2018, S. Cakmakyapan et al demonstrated a graphene photodetector with high responsivity over a wide wavelength regime (0.6 A W −1 at 0.8 µm and 11.5 A W −1 at 20 µm), setting a record of the widest photodetection bandwidth with high responsivity up to date . The structure is shown in figures on the left of Figure a, in which the metal electrodes are designed so that the incident light can be concentrated in the graphene channels within a broad spectrum from 0.8 to 20 µm, shown in the top right panel of Figure a.…”
Section: Polaritons In 2d Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, nonzero net photocurrent can be generated without applying bias voltage, solving the dark current problem. In 2018, S. Cakmakyapan et al demonstrated a graphene photodetector with high responsivity over a wide wavelength regime (0.6 A W −1 at 0.8 µm and 11.5 A W −1 at 20 µm), setting a record of the widest photodetection bandwidth with high responsivity up to date . The structure is shown in figures on the left of Figure a, in which the metal electrodes are designed so that the incident light can be concentrated in the graphene channels within a broad spectrum from 0.8 to 20 µm, shown in the top right panel of Figure a.…”
Section: Polaritons In 2d Materialsmentioning
confidence: 99%
“…b) Fast and high‐sensitivity gas identification by graphene molecule sensor. a) Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Polaritons In 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are limited by material nonuniformity, significant 1/f noise, and intrinsic low‐speed response. Recently, 2D material photodetectors have attracted a lot of attention, but they are not yet at the state of the art and moreover far from presenting a mature and reproducible fabrication process . Quantum well infrared photodetectors (QWIPs) based on GaAs/AlGaAs heterostructures have a competitive background‐limited detectivity (10 10 cm Hz 1/2 W −1 ) and a very high‐frequency response up to 100 GHz, due to their intrinsic short carrier lifetime (few ps) .…”
Section: Introductionmentioning
confidence: 99%